Enhancing AA6061–Bottom Ash Composites: Role of Heat Treatment on Properties and Dimensional Stability - Seputro, Harjo; Bintoro, Sefrian R.; Ariawan, Dody; Surojo, Eko; Triyono (Salehan Institute of Higher Education, 2025)
Aluminum matrix composites (AMCs) reinforced with industrial by-products have attracted attention as lightweight, sustainable materials, yet most research has focused on fly ash. The higher density of bottom ash compared to fly ash makes bottom ash suitable for use as reinforcement in AMC. This study investigates the combined effect of BA reinforcement (0, 3, and 6 wt%) and T6 heat treatment (aging at 175, 200, and 225 °C) on the microstructure, mechanical performance, thermal expansion, and dimensional stability of AA6061 composites. Mechanical testing, thermomechanical analysis (TMA), and coordinate measuring machine (CMM) evaluations were conducted to establish correlations between microstructure and macroscopic reliability. The results show that aging plays a decisive role in strengthening and stabilizing the alloy. The unreinforced AA6061 achieved peak hardness (69.43 BHN) and tensile strength (274.60 MPa) at 200 °C, but exhibited the largest distortion due to high thermal expansion. BA addition significantly reduced the mean coefficient of thermal expansion, with the 3 wt% BA composite aged at 200 °C demonstrating the most balanced behavior: stable CTE response, minimal distortion (0.1–0.4 mm²), and improved mechanical reliability. In contrast, 6 wt% BA composites, despite their lowest mean CTE (≈25 ppm/K), suffered from local instabilities due to particle agglomeration and porosity, leading to reduced toughness and higher geometric irregularities. Overall, this work highlights the novelty of employing BA as a sustainable reinforcement distinct from fly ash, showing that moderate BA addition coupled with optimized heat treatment can enhance dimensional stability and mechanical performance. The findings provide new insights into the design of cost-effective, environmentally friendly AMCs for structural applications.